On Refuge. (4th July 2018) - Grehan, Helena
Abstract : Artist Naomi Hamer explores complex questions surrounding ideas of response and responsibility in her artwork Mandatory/Monument . Hamer's large-scale installation draws attention to the Australian government's policy of mandatory detention of asylum seekers and refugees – largely in offshore sites away from the public eye. Each of her five large orange crocheted banners has the name of a detention centre woven into it. They sit boldly in the performance space and draw the attention of spectators to that which is largely hidden or made invisible by distance, isolation and governmental refusal. Whilst these banners are in themselves arresting, Hamer further complicates things by actively completing the banners during the installation and then inviting spectators to unravel these on the final day. The questions asked here surround the act and politics of unravelling or of abstaining.